Tüketicinin korunması hakkında kanun kapsamında ayıplı maldan sorumlulukta tüketicinin sözleşmeden dönme hakkının sınırları - Kol, Yavuz Selim (My University, 2023)
Belirli bir hukuki neticeye varma niyetiyle sözleşme kuran tarafların sözleşmeye aykırı birtakım davranışlar sebebiyle edim menfaatine ulaşamamaları ve dolayısıyla edim ve karşı edim arasında sözleşmenin kuruluşu aşamasında mevcut olan dengenin bozulması söz konusu olmaktadır. Bu dengeyi bozan sözleşmeye aykırı davranışlardan biri de satılanın ayıplı bir şekilde teslim edilmesi olup bu durumda sözleşme ile bağlılığını sürdürme niyetinde olmayan tüketicinin başvuracağı yol ise sözleşmeden dönmedir. 6502 sayılı TKHK m. 11 hükmünde de tüketiciye satılanı geri vermeye hazır olduğunu bildirerek sözleşmeden dönme imkanı tanınmış ve ayrıca satıcının, tüketicinin tercih ettiği bu talebi yerine getirmekle yükümlü olduğu madde hükmünde vurgulanmıştır. Adi satış sözleşmeleri bakımından da belirli şartlar altında alıcıya tanınan bu hak bakımından Türk Borçlar Kanunu’nda birtakım sınırlar getirilmiş olmakla birlikte TKHK’da tüketicinin sözleşmeden dönme hakkını sınırlandıran bir hüküm yer almamaktadır. Mevcut durumda tüketici tarafından sözleşmeden dönme hakkının herhangi bir sınırlandırmaya tabi olmadan kullanılmasının imkanı görünmemektedir. Bu çalışma kapsamında TKHK m. 83 hükmünde kanunda hüküm bulunmayan hallerde genel hükümlere yapılan atıf da dikkate alınarak; durumun sözleşmeden dönmeyi haklı göstermemesi, ayıpsız bir benzerinin hemen verilerek ve uğradığı zararın tamamı giderilerek seçimlik hakların kullanımının engellenmesi, ayıplı satılanın iade edilememesi, sınırlı dönme kuralı, sorumsuzluk anlaşmaları, zamanaşımı kuralı, kullanım hatası ve malın kullanılması başlıkları altında hangi şartlarda tüketicinin sözleşmeden dönme hakkının sınırlandırılabileceği irdelenecektir.

The parties that conclude a contract with the intention of reaching a certain legal result cannot achieve the performance benefit due to certain acts contrary to the contract, and therefore, the balance between the performance and counter performance at the stage of the establishment of the contract is disturbed. One of the acts contrary to the contract that disrupts this balance is the defective delivery of the sold product, and in this case, the way to be resorted to by the consumer who does not intend to continue his commitment to the contract is to withdraw from the contract. Law on Protection of the Consumers in article 11, the consumer is given the opportunity to withdraw from the contract by declaring that he is ready to return the sold product, and it is also emphasized in the provision of the article that the seller is obliged to fulfill this demand preferred by the consumer. The parties that conclude a contract with the intention of reaching a certain legal result cannot achieve the performance benefit due to certain acts contrary to the contract, and therefore, the balance between the performance and counter performance at the stage of the establishment of the contract is disturbed. One of the acts contrary to the contract that disrupts this balance is the defective delivery of the sold product, and in this case, the way to be resorted to by the consumer who does not intend to continue his commitment to the contract is to withdraw from the contract. Law No. 6502 on the Protection of Consumers m. In Article 11, the consumer is given the opportunity to withdraw from the contract by declaring that he is ready to return the sold product, and it is also emphasized in the provision of the article that the seller is obliged to fulfill this demand preferred by the consumer. In terms of ordinary sales contracts, although some limits have been set in the Turkish Code of Obligations in terms of this right granted to the buyer under certain conditions, there is no provision in the TKHK that limits the consumer's right to withdraw from the contract. In the current situation, it is not possible for the consumer to use the right to withdraw from the contract without any limitations. Within the scope of this study, considering TKHK m. 83, the reference to general provisions in cases where there is no provision in the law; it will be examined under which conditions the consumer's right to withdraw from the contract be limited under the headings of the situation not justifying the withdrawal from the contract, preventing the use of optional rights by immediately giving a non-defective similar and eliminating all the damage, non-refundability of the defective product, limited return rule, irresponsibility agreements, statute of limitations, usage error and use of the goods. will be examined.
Limits of the consumer's right to withdraw in liability for defected goods within the scope of TKHK
Keywords: Consumer; Consumer contracts; Consumer protection; dönmenin sınırları; durumun dönmeyi haklı göstermemesi; inability to return; Law and legislation; limits of the withdrawal; malın kullanılmasının etkisi; nonliability agreements; satılanın iade edilememesi; situations does not justify the withdrawal; sorumsuzluk anlaşması; sözleşmeden dönme; the; the effect of using the goods sold; the right to withdraw; Turkey; Tüketici; Tüketici sözleşmeleri; Tüketicinin korunması; Türkiye; Yasa ve yasama